PEDAGOGICAL TRENDS ANALYSIS IN PEDAGOGICAL PRACTICES OF PHYSICAL EDUCATION'S TEACHERS (Fiep Bulletin - online, 2014)
This paper has the objective to analyze Pedagogical Trends in Physical Education within Pedagogical Trends in Generall Education classified by Libâneo.We discuss, using the experience of the authors and the current bibliography, how these trends influence the pedagogical practices of physical education. We conclude that social abilities (solidarity, respect, socialization etc.) through the corporal culture of human movement in its diverse manifestations must be worked, having as objective the development of physical aptitude and formation of the citizenship in a pleasant way.
Keywords: pedagogical trends; physical aptitude; health